Balanced Shifts - Ahmadi Dastjerdi, Dawoud; Shahamat, M. (Communications in Mathematics and Applications, 2020)
The notion of the balanced generator of the Dyke system (or Dyck system) has been extended to a general subshift called balanced shift and it has been shown that they are essentially mixing. All balanced shifts are half synchronized and full shifts are the only balanced and synchronized subshifts. Also, a formula for the Gurevic entropy of a balanced shift has been given.